Wars and Rumors of (preemptive) Wars - Seiple, Chris (2003)
In today's world where security concerns dominate political decision-making, Christians often grapple with the issue of just war. It is particularly difficult, but not impossible, to discern the basis for a just preemptive war. Three principles guide this discussion: human nature has a great capacity for violence; the purpose of governments is to protect their people; and God cares about justice. It is a moral responsibility to develop a doctrine of preemption to guide our approach to national security issues.
Keywords: Security; Terrorism; Theology; War